Pengaruh Pengetahuan Perpajakan, Penghargaan Finansial, dan Efikasi Diri terhadap Minat Mahasiswa Akuntansi Berkarier di Bidang Perpajakan - Vishwamitra, I Gusti Ngurah Premananda; Mimba, Ni Putu Sri Harta (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to analyze the influence of taxation knowledge, financial rewards, and self-efficacy, on accounting students' interest in a career in taxation. This research is located at the Faculty of Economics and Business, Udayana University. Data collection was conducted using a survey method using a questionnaire. The number of respondents was 275 students selected through nonprobability sampling method with saturated sampling technique or census. Structural Equation Modeling (SEM) based on Partial Least Square (PLS) approach was used to analyse data with the help of SmartPLS software. The results show that taxation knowledge, self-efficacy, and financial rewards have a significant positive influence on accounting students' interest in a career in taxation.